Design And Development of Help Patient Data Management Information System at Sinergi Atap Negeri Foundation Web-Based Using Codeigniter - Miliardi Zonna Ar Rikiti; Eden Kusmayanto; Rina Kurniawati (Yayasan Riset dan Pengembangan Intelektual (YRPI), 2022)
The Sinergi Atap Negeri Foundation is a legal and independent non-profit social foundation with the goal of becoming a halfway house facilitator for needy patients and families. The purpose of this study is to create a data management information system for assisted patients to aid in data management, patient submissions, and data transactions at the Sinergi Atap Negeri Foundation, thereby making work more effective and efficient. The waterfall method is used in software development to collect data from previous studies through observations, interviews, and literature studies. The Sinergi Atap Negeri Foundation's patient data management system, according to the analysis, is still manual, whereas previously data management could only be managed by one foundation administrator and accessed by anyone. Given these concerns, researchers are encouraged to develop a web-based application using PHP, the Codeigniter 3 framework, and Mysql as a database. It is hoped that this information system will improve the performance of foundation employees by making data entry easier and faster, as well as avoiding data loss errors from a security standpoint.